#2 10:20 of that helps can u help me on my question
Answer:
Simplifying
6n + 7 + -2n + -14 = 5n + 1
Reorder the terms:
7 + -14 + 6n + -2n = 5n + 1
Combine like terms: 7 + -14 = -7
-7 + 6n + -2n = 5n + 1
Combine like terms: 6n + -2n = 4n
-7 + 4n = 5n + 1
Reorder the terms:
-7 + 4n = 1 + 5n
Solving
-7 + 4n = 1 + 5n
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '-5n' to each side of the equation.
-7 + 4n + -5n = 1 + 5n + -5n
Combine like terms: 4n + -5n = -1n
-7 + -1n = 1 + 5n + -5n
Combine like terms: 5n + -5n = 0
-7 + -1n = 1 + 0
-7 + -1n = 1
Add '7' to each side of the equation.
-7 + 7 + -1n = 1 + 7
Combine like terms: -7 + 7 = 0
0 + -1n = 1 + 7
-1n = 1 + 7
Combine like terms: 1 + 7 = 8
-1n = 8
Divide each side by '-1'.
n = -8
Simplifying
n = -8
Step-by-step explanation:
Answer:
(150, 100) is the solution for the system of equations
Step-by-step explanation:
Without more context, I cannot give you an exact answer, but this graph shows the solution to a system of equations. When y is 100, x is 150.
Have a nice day!
I hope this is what you are looking for, but if not - comment! I will edit and update my answer accordingly.
- Heather
Answer:
D
Step-by-step explanation:
Ordenered pairs g(x):
(0,0); (2,2); (- 2,2)
g(x) = ax² + bx + c
(0,0)
a.0² + b.0 + c = 0
c = 0
(2,2)
a.2² + b.2 + c = 2
4a + 2b = 2
(- 2,2)
a.(- 2)² + b.(- 2) + c = 2
4a - 2b = 2
4a + 2b = 4a - 2b
2b + 2b = 0
4b = 0
b = 0
4a + 2b = 2
4a = 2
a = 2/4
a = 1/2
g(x) = 1/2x² + 0x + 0
g(x) = 1/2x²
I hope I've helped you.
Answer:
your handwriting is too worse I can't see it properly